Evaluation, regeneration and enhanced database management of unique resources from Mesoamerica: progress report (April 1998 - December 1998) - CATIE - Centro Agronómico Tropical de Investigación y Enseñanza, Turrialba, Costa Rica (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
7 tab.